Microeconomic analysis and bioeconomic modeling of the Senegalese sardinella artisanal fishery - (:unkn) unknown (My University, 2017)
Small pelagic fish are the main fish resource in North West Africa. In Senegal, they are mainly represented by the sardinellas (Sardinella aurita and S. maderensis). The fishery, mostly composed by purse seins and encircling gill nets, is predominantly performed by artisanal fishers and is of great importance for the Senegalese economy and for food security in the region. However, the last fish stock assessment has shown a decrease of the biomass and an overexploitation status for the West African Sardinella resource. In such context, the operating conditions for this fishery have changed during the recent years, thus a profitability analysis of this Senegalese fishery is performed and a bioeconomic model is developed to simulate the dynamics of sardinella exploitation. This model will allow managers and decision makers to analyze the responses of the fishery to economic (price, costs), biologic (growth, mortality, recruitment) and management (tax, subsidies, licenses, spatial regulations) parameters. The profitability analysis over the last twenty years show that the fisheries had considerably lost in profitability (65 to 100 %) while the operating costs increased by 25 and 90 % for encircling gillnet and purse seine, respectively. The bioeconomic model shows a high overcapacity in the fishery; on this basis, to achieve the goal of optimizing the fishery exploitation according to socio-economic and sustainability objectives we recommend to reduce the fishing capacity by 50 %. Our results showed that for management measures the freeze or decrease of fishing effort allows for better results in terms of profit, rent, and individual income for the fishermen but also promotes a sustainable exploitation. The resources studied in this work are shared among several countries, our future perspective is to apply our approach to the whole distribution area of the species in the sub-region. This can be done by means of concerted studies with the countries sharing
Keywords: African Research